Honey-- honey-- lion! : a story from Africa - Brett, Jan, 1949- (G.P. Putnam's Sons, 2005)
After working together to obtain honey, the African honey badger always shares it with his partner, the honeyguide bird, until one day when the honey badger becomes greedy and his feathered friend decides to teach him a lesson.